AGE FACTOR IN A MATH CONTEST PAPER FOR 5TH AND 6TH GRADE STUDENTS - Lazarov, Borislav; Vasileva, Albena (Matematichki Bilten, 2016)
The format of the Chernorizec Hrabar Math Tournament includes 5 divisions for students of two consecutive grades, e.g. 5th and 6th grade students. A natural question is how appropriate is the common competition paper for any of two age strata. To clarify this issue we introduce the notion of age-factor index as the difference of the test-item difficulties calculated separately for any age stratum, e.g. \(Δ^k=T_5^k-T_6^k\) where \(T_5^k\) and \(T_6^k\) stand for the test-item difficulty of the \(k\)-th test item for the 5th and 6th grade students’ variation row respectively. The average value of \(Δ^k\) for the contest paper could be considered as a relative measure of reliability and uniformity of the contest paper for a particular target group. The study presents details about 2015 Chernorizec Hrabar contest paper for 5th and 6th graders and the application of the new concept in didactical analysis.